Tinjauan Aspek Disposisi dan Struktur Birokrasi dalam Kebijakan Bebas Asap Rokok - Nurul Hikmah B; Harpiana Rahman; Sartika Sartika; Ayu Puspitasari; Mansur Sididi; Nur Ulmy Mahmud; Christa Gumanti Manik (FORIKES, 2022)
Indonesia is one of the countries with the largest cigarette consumption in the world. The purpose of this study is to review aspects of the disposition and structure of the bureaucracy in a smoke-free policy during the pandemic that has been realized by the government. This research was a descriptive research. Data were collected through filling out questionnaires containing respondents' characteristics (age, education and type of cigarette), disposition and bureaucratic structure of cigarette smoke control policies in public areas. Data were analyzed descriptively in the form of frequency and percentage. The results of this study found that 69.1% of adolescents aged 16-18 years consumed the most cigarettes, with a high school education level (61.7%). Tobacco cigarettes are the most popular type of youth (48.9%). Around 37.2% of the attitude/disposition of policy implementers stated that the implementation of smoke-free policies was poor during the pandemic. The involvement of the government bureaucratic structure is less (23.4%). Overall, the majority of adolescents stated that the disposition and bureaucratic structure of the government did not provide significant changes in the implementation of smoke-free policies in public spaces.Keywords: smoke free; disposition; bureaucratic structure ABSTRAK Indonesia menjadi salah satu negara dengan konsumsi rokok terbesar di dunia. Tujuan penelitian ini adalah untuk meninjau aspek disposisi dan struktur birokrasi dalam kebijakan bebas asap rokok di masa pandemi yang telah direalisasikan oleh pemerintah. Penelitian ini merupakan studi deskriptif. Data dikumpulkan melalui pengisian kuesioner yang berisi tentang karakteristik responden (usia, pendidikan dan jenis rokok), disposisi dan struktur birokrasi terhadap kebijakan pengendalian asap rokok di area-area publik. Data dianalisis secara deskriptif berupa frekuensi dan persentase. Hasil penelitian ini menemukan bahwa 69,1% remaja usia 16-18 tahun yang paling banyak mengkonsumsi rokok, dengan tingkat pendidikan SMA (61,7%). Rokok tembakau adalah jenis paling diminati remaja (48,9%). Sekitar 37,2% sikap/disposisi dari pelaksana kebijakan menyatakan buruknya penerapan kebijakan bebas asap rokok di masa pandemi. Keterlibatan struktur birokrasi pemerintah adalah kurang (23,4%). Secara keseluruhan, mayoritas remaja menyatakan disposisi dan struktur birokrasi yang dilakukan pemerintah tidak memberikan perubahan signifikan dalam penerapan kebijakan bebas asap rokok di ruang publik.Kata kunci: bebas asap rokok; disposisi; struktur birokrasi